ANALISIS PERTANDINGAN BULUTANGKIS FINAL TUNGGAL PUTRA PADA OLIMPIADE MUSIM PANAS XXX DI LONDON 2012 - Putri, Hikmah Nindya (Jurnal Kesehatan Olahraga, 2014)
In the badminton match analysis, there unforced error be weapon in the match to get a winner point, and there forced error be one factor to be lose. The purpose of this study to analysis unforced error and forced error of Lee Chong Wei and Lin Dan, includes service, lob, dropshot, smash, drive, backhand, and netting. Types of study makes qualitative approach and simple quantitative approach if possible with descriptive method, while this study is document analys form secondary data. Data analysis result analyzed a number by percentage formula, while analyzed a picture by sorftware Dartfish. Data analysis result show unforced error the percentage of Lee Chong Wei by 46,73% and the forced error by 53,27%. Dominated forced error percentage of Lee Chong Wei is return smash by 14%. In contrast to Lin Dan had unforced error the percentage by 53,27% and the forced error by 46,7386%. Dominated forced error percentage of Lin Dan is lob by 13,08%. The conclution of this study is that badminton match was won by Lin Dan with a score 2-1 over Lee Chong Wei. Stroke technique that dominated unforced error both smash by 15-18%, while dominated forced error of Lee Chong Wei was  return smash and dominated forced error of Lin Dan was lob. It is because improper body position to hit the ball so that the roght of return or not widen(out), and the ball movement in difficult position to return the opposite area. Key Word : Analysis, Badminton match